2021
DOI: 10.1111/jfpp.15244
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrocolloids on the rheological and textural attributes of a gluten‐free meat analog based on soy protein isolate

Abstract: This study investigated the influence of gluten substitution on the rheological and textural attributes of a soy protein isolate-based meat analog. Five different hydrocolloids (guar gum (G),-carrageenan (C), xanthan gum (X), hydroxypropyl starch (HPS), and cross-linked tapioca starch (CLS)) were added (1%-7% w/w) to the meat analog and compared with a control sample containing 7% w/w gluten (0% hydrocolloid). Adding the hydrocolloids increased the viscosity and degree of plasticity of the meat analog compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…A study on SPI-based meat analogues, designed to find hydrocolloids suitable to replace gluten in the recipe, found that the addition of 1-4% hydroxypropyl starch and cross-linked starch decreased the hardness, gumminess, springiness, and cohesiveness of the extruded meat analogues. [94] The changes in textural properties were found to correlate well with the rheological data they obtained directly from the extruder. The starches were not found to be suitable replacers for gluten in the recipes, unlike blends of other hydrocolloids.…”
Section: Textural Propertiessupporting
confidence: 61%
“…A study on SPI-based meat analogues, designed to find hydrocolloids suitable to replace gluten in the recipe, found that the addition of 1-4% hydroxypropyl starch and cross-linked starch decreased the hardness, gumminess, springiness, and cohesiveness of the extruded meat analogues. [94] The changes in textural properties were found to correlate well with the rheological data they obtained directly from the extruder. The starches were not found to be suitable replacers for gluten in the recipes, unlike blends of other hydrocolloids.…”
Section: Textural Propertiessupporting
confidence: 61%
“…Not only isolated but especially less refined forms of soy protein such concentrates are used in extrusion applications [26,27]. With the use of an isolate, in several cases, additional components such as wheat gluten or carbohydrate fibres, are used for the formation of a multi-phase blend [28,29]. The mechanism of fibre formation is then based on the alignment of those phases [25].…”
Section: Chicken-like and Steak-like Productsmentioning
confidence: 99%
“…%1-7 hidrokolloid ilaveli et analoğu numunelerinde, kayma hızı arttıkça viskozitenin azalarak psödoplastik davranış gösterdiği bildirilmiştir. Eklenen miktara bağlı olarak guar gam ve ksantan gamın, et analoğunun dokusal özellikleri üzerinde hidroksipropil nişasta ve çapraz bağlı tapyoka nişastasından daha büyük bir etkiye sahip olduğu belirtilerek, soya proteini izolatı bazlı et analoglarının, tüketici kabulünü kazanmak için gluten eklemeye ihtiyaç duymadan da hidrokolloid varlığında geliştirilebileceği bildirilmiştir [137].…”
Section: Hidrokolloidler Ve Bitki Protein Kombinasyonlarıunclassified